Need to enrich your vocabulary? Use wordsift / Noraziah Azizan, Shazila Abdullah, Sheema Liza Idris and Nur Hazirah Mohd Fuat - Azizan, Noraziah; Idris, Sheema Liza; Mohd Fuat, Nur Hazirah (2022)
Reading is one of the most important language skills that every language learner needs to be competent at to enable them to understand a reading text well. It involves a manifold of processes, which begin with word recognition, leading to comprehension, fluency, and finally motivation. These processes may require some demanding tasks, especially for second language learners. Even at the word recognition level, if learners are not able to recognise the words, they might not be able to comprehend the text. This is further strengthened by the fact that second language learners often have a low repertoire of vocabulary, which is probably due to implicit teaching of vocabulary in the classroom. Therefore, language instructors need to find a technique that will help learners to not only recognise the words, but also enrich their vocabulary. This paper, hence, aims to introduce a digital teaching technique called WordSift that is both fun and educational, easily accessible online and can be used at various levels. We used the WordSift application on six-second language learners from the pre-diploma course at UiTM Perak Branch to explore the possibility of using this on a larger group of students. A pretest and posttest are used to evaluate whether the technique used can help enhance their vocabulary knowledge. The results would be indicative of whether WordSift could be a teaching innovation that could help learners enhance their vocabulary enrichment.